Identification of Factors Affecting Household Waste Management for SDGs Achievements in North Sumatra - Zahrotun Niawaroh; F Rooslan Edy Santosa (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
Management Program is often proclaimed rarely done among the people, it becomes a question mark what is the cause and origin. Based on the problematic, research was carried out in the North Surabaya area .Where this region, most people still throw trash in place that should not be. The purpose of this study is to determine the pattern of waste management environment of the community. What is the pattern of society in waste management as well as factors that affect the community in waste sorting. The method in this research is descriptive qualitative. Based on this research, factors that encourage people to sort the waste are busyness factor, level of education, age housewives as a principal dividing owned along with the number of children, and the lack of media information obtained.